Gamyflip-pro module: teaching and learning through flipped classroom and gamification approach / Azia Sulong, Abu Bakar Ibrahim and Ashardi Abas - Sulong, Azia; Ibrahim, Abu Bakar; Abas, Ashardi (2020)
In recent years, the integration of Flipped Classroom and gamification in teaching and learning process became popular in order to provide flexibility in teaching and learning process. The purpose of this innovation was to introduce GamyFlip-Pro module in teaching and learning a topic Programming for preuniversity students. This module consists of two separate manuals; teacher manual and student manual. The objective of development GamyFlip-Pro module are to increase motivation and student engagement in learning programming (Problem solving), provide step by step guideline for teachers and student to implement teaching and learning using gamified flipped classroom approach and produce teaching and learning environment that interactive and educate “Fun Learning” to the teachers and students. This module was developed based on Sidek and Jamaludin’s Model, Flipped Classroom Approach, and The Five Steps of Applying Gamification in Education by Huang and Soman. Since the development of module draft complete, five subject matter experts will review the module draft. Then, module modification was done based on suggestion and recommendations by subject matter experts. This module tested to 30 students and the finding shows that GamyFlip-Pro module has a good impact to the student achievement (83.72%), motivation (4.67) and level of engagement (4.65). This finding reinforces the use of flipped classroom and gamification approach in the design of teaching and learning modules and establish the pedagogy of flipped learning and gamification in teaching programming.